Pengendalian Internal Meminimalisir Financial Statement Fraud Melalui Sistem Informasi Akuntansi Penggajian di RSU Muhammadiyah Ponorogo - Titi Rapini; Umi Farida; Rizki Listyono Putro (Politeknik Ganesha Medan, 2022)
The purpose of this study is to analyze how the application of the payroll accounting information system at the Muhammadiyah Ponorogo General Hospital, and how the system supports internal control efforts in the company. The methodology used in this research is descriptive qualitative, using interview, documentation, and observation techniques. The results of the study explain the findings in the field related to the payroll accounting information system, showing that there is a separation of duties in the organizational structure that is responsible for managing employee finances, namely the SDI sub-section (my source is human), the accounting sub-section, and the treasury sub-section. The SDI subdivision (my source is human), is responsible for recording employee attendance using a finger print, as well as recapitulating employee attendance every month to make a list of employee salaries, then submitting the accounting subdivision. The accounting subdivision is responsible for making records relating to salary payments such as salary payables and tax payables, as well as re-examining the payroll made by the SDI section and issuing orders for spending money and forwarded to the treasury subsection for payroll payments and recording money out . The treasury subdivision is responsible for paying employee salaries through the bank by transferring money directly to each employee's account, as well as providing proof of transfer to the accounting subdivision to record outgoing money through the recording system. So the payroll accounting information system at the Ponorogo Muhammadiyah General Hospital shows that it supports internal control efforts that are quite good, there is a clear separation of duties in the organizational structure responsible for managing finances. Expected to be able to compile financial reports that can be accounted for to stakeholders, carry out salary payments on time and can minimize financial statement fraud.